Racemization barriers of 1,1'-binaphthyl and 1,1'-binaphthalene-2,2'-diol: a DFT study - Meca, Ludek; Reha, David; Havlas, Zdenek (The Journal of organic chemistry, 2003)
Density functional theory has been applied to the study of various pathways and transition states for the configurational inversion of 1,1'-binaphthyl (1) and 1,1'-binaphthalene-2,2'-diol (2). The preferred pathway is found to be anti with centrosymmetric transition state. Whereas the reaction path of 1 goes downhill from transition to ground state, in the case of 2 it contains one unexpected local minimum. Very satisfactory agreement with available experimental values of activation Gibbs energies is achieved.